HUBUNGAN ANTARA POLA KONSUMSI DAN AKTIVITAS FISIK TERHADAP STATUS GIZI PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA JARA MARA PATI BULELENG - I Gede Ariyasa; I Nengah Sandi; I Made Murna (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2017)
Background: Age of hope hudup Indonesian population is increasing. The increase is due to a balanced pattern of consumption and physical activity. Objective: This study aims to determine the effect of consumption patterns and physical activity on nutritional status in the elderly. Method: This research is an analytic study that describes the relationship between independent variables with dependent variables using linear regression analysis berbanda. The study was conducted on 64 elderly Social Home Tresna Werdha Jara Mara Pati Buleleng District, Bali. Begin by interviewing respondents, then asked respondents to fill out questionnaires. Further measurement of body mass index (BMI). Results: There was a partial and positive relationship between consumption pattern and nutritional status with r = 0,761 and p = 0.000. There was a partial and positive relationship between physical activity and nutritional status with r = 0.262 and p = 0.000. In addition, there was also a simultaneous relationship between consumption patterns and physical activity on nutritional status of 91.5% with a value of R = 0.958. Conclusion: Partial and simultaneous relationship exists between consumption patterns and physical activity on nutritional status. Suggestion: For that it is expected in the elderly to always maintain the pattern of consumption and physical activity regularly in order to improve nutritional status.